Relational Thinking of College Students in Solving Recurrence Relation Problems Using Hanoi Tower Props - Nur Fitriyah Indraswari; Fitriana Minggani (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
The purpose of this study is to describe how college students with visual, auditory, and kinaesthetic learning style think relationally in solving recurrence relation problems using the tower of Hanoi. This study is an exploratory with a qualitative descriptive approach. It began by the provision of a mathematics ability test and a learning style questionnaire to obtain three subjects, each of which had a different learning style but equivalent mathematics ability. Next, the three subjects were given problem-solving tasks and interviewed twice. Time triangulation is used to check the consistency of the data. After the validity of the data had been confirmed, the analyses were executed. The data analysis stage of this study consists of five stages: data categorisation, data reduction, data presentation, data interpretation, and conclusion. The result shows that all three subjects met the four indicators of relational thinking, were Understand the problem, make a plan completion, carry out the completion plan, and recheck completion but only the kinaesthetic subject managed to find the final answer.